Emission Area Patterning of Organic Light‐Emitting Diodes (OLEDs) via Printed Dielectrics. (25th July 2018) - Han, Donggeon; Khan, Yasser; Gopalan, Karthik; Pierre, Adrien; Arias, Ana C.
Abstract: Solution‐processibility is one of the distinguished traits of organic light‐emitting diodes (OLEDs) compared to existing solid‐state LED technologies. It allows new opportunities which can simplify the fabrication and potentially reduce the cost of manufacturing process. Emission area patterning is one of the crucial fabrication steps and it usually involves subtractive methods, such as photolithography or etching. Here, printing techniques are used to pattern the emission area of blade‐coated OLED layers. The print qualities of a number of printing schemes are characterized and compared. Spray coating and screen printing are used to deposit dielectrics with desired patterns on the OLED layers. At luminance of 1000 cd m −2 the OLEDs patterned using spray‐coated and screen‐printed dielectric show current density of 8.2 and 10.1 mA cm −2, external quantum efficiency (EQE) of 2.1% and 2.1%, and luminous efficacy of 5.5 and 6.3 lm W −1, respectively. The OLED characteristics and features of each printing scheme in depositing the dielectric layer are discussed. The printing methods are further applied to demonstrate displays with complex shapes and a seven‐segment display. Abstract : The emission area of organic light‐emitting diode (OLED) is patterned by printed dielectrics using various printing schemes. The dielectric layers deposited via spray coating and screen printing are characterized in terms of their print quality using various concentrations of inks. Then, these patterning techniques are used to create OLED with a logo and a seven‐segment display.